Mortality in HIV-infected women, heterosexual men, and men who have sex with men in Rio de Janeiro, Brazil: an observational cohort study. Issue 10 (October 2016) - Coelho, Lara; Grinsztejn, Beatriz; Castilho, Jessica L; De Boni, Raquel; Quintana, Marcel S B; Campos, Dayse P; Ribeiro, Sayonara R; Pacheco, Antonio G; Veloso, Valdilea G; Luz, Paula M
Summary: Background: Mortality in HIV-infected individuals might differ by sex and mode of HIV acquisition. We aimed to study mortality in HIV-infected women, heterosexual men, and men who have sex with men (MSM) in a cohort from Rio de Janeiro, Brazil. Methods: In this observational cohort study, we included HIV-infected women, heterosexual men, and MSM (aged ≥18 years) from the Instituto Nacional de Infectologia Evandro Chagas database who were enrolled between Jan 1, 2000, and Oct 30, 2011, and who had at least 60 days of follow-up. Causes of deaths, defined with the Coding of Death in HIV protocol, were documented. Cox proportional hazards models accounting for competing risks were used to explore risk factors for AIDS-related and non-AIDS-related deaths. Findings: We had 10 142 person-years of follow-up from 2224 individuals: 817 (37%) women, 554 (25%) heterosexual men, and 853 (38%) MSM. Of 103 deaths occurred, 64 were AIDS related, 31 were non-AIDS related, and eight were of unknown causes. In unadjusted analyses, compared with women, the hazard of AIDS-related deaths was higher for heterosexual men (hazard ratio [HR] 3·52, 95% CI 1·30–9·08; p=0·009) and for MSM (2·30, 0·89–5·94; p=0·084). After adjustment for age, CD4 cell counts, last HIV viral load, antiretroviral therapy use, and AIDS-defining infection, AIDS-defining malignant disease, and hospital admission during follow-up, the excess risk of AIDS-related death decreased for heterosexual men (adjusted HR 1·99, 0·75–5·25; p=0·163) but was unchanged for MSM (2·24, 0·82–6·11; p=0·114). Non-AIDS-related mortality did not differ by group. Interpretation: Compared with women, increased risk of AIDS-related death in heterosexual men was partly mitigated by risk factors for AIDS mortality, whereas the excess risk in MSM was unchanged. Further study of reasons for disparity in AIDS-related mortality by mode of transmission is needed. Funding: US National Institutes of Health, Brazilian National Council of Technological and Scientific Development (CNPq), and Research Funding Agency of the State of Rio de Janeiro (FAPERJ).